Análisis a los Estados Financieros a la Industria Lojana de Especerías ILE C.A Periodos 2020-2021” - Luzuriaga León, Eduardo Sebastián (2023)
The curricular integration work has as its objective to apply the process of "FINANCIAL ANALYSIS TO INDUSTRIA LOJANA DE ESPECERÍAS ILE C.A PERIODS 2020-2021", allowed to know its economic-financial situation with the application of the vertical and horizontal method and financial indicators, for the correct decision making by its general manager, it will allow knowing the variations presented during the analyzed periods. According to the stated objectives, we obtained all the necessary information to perform the vertical analysis of the established periods, limiting the values of each account according to the group to which it belongs; we also unveiled how the Financial Statements are composed, which are of vital importance to evaluate the economic and financial situation of the company, we also developed the horizontal analysis, here we determined the variations, that is to say, the increases and decreases in the values of the Financial Statements in the periods 2020 and 2021. Afterward, the Financial Indicators were applied, which are the indicators that allow the economic and financial situation of the company; among the indicators implemented are Liquidity, Activity, Indebtedness, and Profitability, in which we detailed each one of them with their respective interpretations. Finally, we elaborated a financial report to know the results obtained from the vertical and horizontal analysis and the related finance indicators in which the Liquidity, Activity, Indebtedness, and Profitability Indicators are detailed. The report contains conclusions and recommendations to help the general manager and directors with the operational administration of the company.